An Overview of Electronic Medical Record Completeness in the Management of Fracture Patients - Ginting, Arjuna; Boris, Jey; Pasaribu, Angelia (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Medical records are comprehensive documents that provide detailed information throughout a patient’s hospitalization. The quality of a medical record is determined by its accuracy, completeness, validity, and timeliness. This study aimed to evaluate the completeness of electronic medical records for fracture patients at Santa Elisabeth Hospital, Medan. Samples were selected using simple random sampling and Slovin’s formula. Data analysis focused on patient identity sheets, anamnesis, informed consent forms, and medical resumes. The review of medical record completeness from January to December 2024 revealed 100% completeness for patient identity sheets, 90.8% for anamnesis, and 98.7% for medical resumes. In contrast, informed consent forms had a notably low completeness rate of only 19.7%, particularly in sections requiring patient or family signatures and administrative authorization. These findings highlight the need for targeted improvements, especially in completing informed consent forms, to meet the standards for optimal medical record quality.